Comprehensive thermoeconomic, exergoeconomic, and optimization analyses of direct oxy‐combustion supercritical CO2 intercooled and reheated cycles under design and off‐design conditions - Wahib A. Al‐Ammari (18877408) (2022)
This study presents comprehensive energetic, exergetic, exergoeconomic, and economic (4E) performance analyses for four direct oxy‐combustion (DOC) supercritical carbon dioxide (sCO2) power cycles at design, off‐design, and part‐load conditions. These cycles include the dual recuperator cycle (DRC), intercooling cycle (ICC), partial intercooling cycle (PIC), and reheating cycle (RHC). The analyses were conducted at relatively low turbine inlet temperatures (TIT: 550–750°C) with compressor inlet temperature (CIT) varied from 33°C (wet‐cooling) to 50°C (dry‐cooling). Furthermore, single‐ and multiobjective optimization analyses were conducted for each cycle. At design conditions (high‐pressure of Pc,o = 20 MPa, low‐pressure of Pc,o = 5.4 MPa, TIT = 750°C, CIT = 50°C [dry‐cooling]), the PIC has the highest thermal efficiency (47.78%) compared to 38.36% for DRC, 45.71% for ICC, and 44.39% for RHC. At optimized conditions (Pc,o = 30 MPa, Pc,o = 8 MPa, TIT = 744°C, CIT = 30°C [wet‐cooling]), the ICC shows superior energetic performance (52.08%) compared to 47.97% for DRC, 49.20% for PIC, and 48.62% for RHC. At off‐design conditions with a power demand (PD) of 40% of the design load (50 MW), the thermal efficiency is decreased by 21.82% in DRC, 17.71% in ICC, 22.46% in PIC, and 13.60% in RHC. The ICC has the minimum levelized cost of electricity compared to the other cycles with 5.93 ¢/kWh at design conditions (dry‐cooling), 5.65 ¢/kWh at optimized conditions (wet‐cooling), and 7.2 ¢/kWh at minimum PD (21 MW). Therefore, from an economic point of view, the ICC is recommended as the best power block for a sCO2 power cycle driven by oxy‐combustor at moderate TITs. The study also provides constructive comparisons between the DOC‐sCO2 and indirect (nuclear, solar, and waste heat) sCO2 power cycle systems and the future research directions. Other Information Published in: Energy Science & Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ese3.1101